Indian Political Intelligence (IPI) files, 1912-1950 - Farrington, Anthony (IDC, 2000)
Archival collection of intelligence files concerning the monitoring of organisations and individuals considered a threat to British India. Included are surveillance reports and intercepts from MI6, MI5, and the Special Branch, as well as a large number of intelligence summaries and position papers. The main thrust is anti-communist. Part of the British Library's Oriental & India Office Collections.